Solid electrolyte prepolymerization liquid, solid electrolyte and battery

By using the monomers in the solid electrolyte prepolymerization liquid to cure and crosslink in situ, a solid electrolyte with high thermal stability is formed, which solves the problem of poor heat resistance of existing solid electrolytes and significantly improves the heat resistance and safety performance of the battery.

CN119400948AActive Publication Date: 2025-02-07SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD

Patent Information

Application Number
CN202410217272.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-02-27
Publication Date
2025-02-07
Estimated Expiration
2044-02-27

AI Technical Summary

Technical Problem

The existing solid electrolytes and their solid-state batteries have poor heat resistance, making it difficult to meet the safety and performance needs of batteries at high temperatures.

Method used

A solid electrolyte prepolymer liquid is provided, including a monomer and an electrolyte solution. The electrolyte contains lithium salts, organic solvents and additives. Through in-situ curing and cross-linking of the monomers, a solid electrolyte with high thermal stability is formed.

Benefits of technology

It significantly improves the heat resistance and safety performance of solid electrolytes, can maintain good electrochemical performance at high temperatures, and reduces the risk of thermal runaway in the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400948A_ABST
    Figure CN119400948A_ABST
Patent Text Reader

Abstract

The invention discloses a solid-state electrolyte prepolymerization liquid, a solid-state electrolyte and a battery, the solid-state electrolyte prepolymerization liquid comprises a monomer and an electrolyte, the electrolyte comprises a lithium salt, an organic solvent and an additive, the monomer comprises one or more of compounds with a structural formula shown as a formula (I): # imgabs0 #, and m is any integer from 2 to 8. When the solid electrolyte prepared from the solid electrolyte prepolymerization liquid is used in a battery, the heat resistance and the safety performance of the battery can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a solid electrolyte prepolymer solution, a solid electrolyte and a battery. Background Art

[0002] At present, electrolytes commonly used in electrochemical devices such as batteries include liquid electrolytes and solid electrolytes. Among them, liquid electrolytes have low thermal decomposition temperatures, are flammable, and easily volatilize to form toxic gases when heated, resulting in certain limitations in improving battery safety performance and energy density.

[0003] Solid-state electrolyte (SSE) is a solid ion conductor electrolyte that has high safety, high power density and cyclability due to its lack of toxic organic liquid leakage, low flammability, non-volatility, strong mechanical properties, good thermal stability, easy processability and low self-discharge rate.

[0004] However, the existing solid electrolytes and their solid-state batteries have poor heat resistance and need to be further improved. Summary of the invention

[0005] In view of this, the present application provides a solid electrolyte prepolymer, a solid electrolyte and a battery, aiming to improve the problem of poor heat resistance of the solid-electrolyte prepared from the existing solid electrolyte prepolymer.

[0006] In a first aspect, an embodiment of the present application provides a solid electrolyte prepolymer solution, comprising a monomer and an electrolyte, wherein the electrolyte comprises a lithium salt, an organic solvent and an additive, and the monomer comprises one or more compounds having a structural formula shown in formula (I):

[0007]

[0008] Wherein, m is any integer from 2 to 8;

[0009] L is a linking group selected from a single bond, substituted or unsubstituted -(CH2) n1 -, substituted or unsubstituted -(CH2) n2 CH=CH(CH2) n3 -, substituted or unsubstituted -(CH2) n4 C≡C(CH2) n5 -, substituted or unsubstituted -(CH2) n6 -O-(CH2) n7 -, substituted or unsubstituted -(CH2) n8 CO(CH2) n9 -, substituted or unsubstituted amine, substituted or unsubstituted C3~C 30Cycloalkyl, substituted or unsubstituted aryl having 6 to 60 ring atoms, and substituted or unsubstituted heteroaryl having 6 to 60 ring atoms, or a combination of two or more thereof, wherein n1 to n9 are each independently selected from an integer of 1 to 5;

[0010] R1, R2, and R3 are each independently selected from hydrogen, substituted or unsubstituted C1-C 30 Alkyl, substituted or unsubstituted C3~C 30 The invention also comprises one or a combination of two or more of a cycloalkyl group having 6 to 60 ring atoms and a substituted or unsubstituted aryl group.

[0011] Optionally, in some embodiments, at least one of the following features (1) to (2) is also included:

[0012] (1) L is selected from a single bond, a substituted or unsubstituted -(CH2) n1 -, substituted or unsubstituted -(CH2) n2 CH=CH(CH2) n3 -, substituted or unsubstituted -(CH2) n4 C≡C(CH2) n5 -, substituted or unsubstituted -(CH2) n6 -O-(CH2) n7 -, substituted or unsubstituted -(CH2) n8 CO(CH2) n9 -, substituted or unsubstituted amine, substituted or unsubstituted C3~C 20 Cycloalkyl, substituted or unsubstituted aryl having 6 to 30 ring atoms, and substituted or unsubstituted heteroaryl having 6 to 30 ring atoms, or a combination of two or more thereof, wherein n1 to n9 are each independently selected from an integer of 1 to 5;

[0013] (2) R1, R2, and R3 are each independently selected from hydrogen, substituted or unsubstituted C1-C 20 Alkyl, substituted or unsubstituted C3~C 20 The invention also comprises one or a combination of two or more of a cycloalkyl group having a ring number of 6 to 30 and a substituted or unsubstituted aryl group having a ring number of 6 to 30.

[0014] Optionally, in some embodiments, at least one of the following features (1) to (2) is also included:

[0015] (1) L is selected from a single bond, a substituted or unsubstituted -(CH2) n1 -, substituted or unsubstituted -(CH2) n2 CH=CH(CH2) n3 -, substituted or unsubstituted -(CH2) n4 C≡C(CH2) n5-, substituted or unsubstituted -(CH2) n6 -O-(CH2) n7 -, substituted or unsubstituted -(CH2) n8 CO(CH2) n9 -, substituted or unsubstituted amine, substituted or unsubstituted C3~C 10 Cycloalkyl, substituted or unsubstituted aryl having 6 to 15 ring atoms, and substituted or unsubstituted heteroaryl having 6 to 15 ring atoms, or a combination of two or more thereof, wherein n1 to n9 are each independently selected from an integer of 1 to 5;

[0016] (2) R1, R2, and R3 are each independently selected from hydrogen, substituted or unsubstituted C1-C 10 Alkyl, substituted or unsubstituted C3~C 10 The invention also comprises one or a combination of two or more of a cycloalkyl group having a ring number of 6 to 20 and a substituted or unsubstituted aryl group having a ring number of 6 to 20.

[0017] Optionally, in some embodiments, at least one of the following features (1) to (2) is also included:

[0018] (1) L is selected from a single bond, a substituted or unsubstituted -(CH2) n1 -, substituted or unsubstituted -(CH2) n6 -O-(CH2) n7 -, a substituted or unsubstituted amino group, a substituted or unsubstituted cycloalkyl group, a substituted or unsubstituted aryl group, or a combination of two or more thereof, wherein n1, n6, and n7 are each independently selected from an integer of 1 to 5;

[0019] (2) R1, R2, and R3 are each independently selected from one or a combination of two or more of hydrogen, substituted or unsubstituted C1-C8 alkyl, substituted or unsubstituted C3-C8 cycloalkyl, and substituted or unsubstituted aryl having 6 to 10 ring atoms.

[0020] Alternatively, in some embodiments, L is selected from one or a combination of two or more of the following groups:

[0021] -(CH2) n1 -、-(CH2) n6 -O-(CH2) n7 -、

[0022]

[0023] Among them, L1 to L 19 is a linking group, each independently selected from a single bond, -(CH2) m’- any one of, wherein m' is selected from any integer of 1-5.

[0024] Optionally, in some embodiments, the monomer is selected from one or more compounds represented by the following structural formulas:

[0025]

[0026] Optionally, in some embodiments, at least one of the following features (1) to (7) is also included:

[0027] (1) m is any integer from 2 to 4;

[0028] (2) The lithium salt includes one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluoroborate, lithium bis(oxalatoborate), and lithium difluorooxalatoborate;

[0029] (3) the organic solvent comprises one or more of a carbonate organic solvent and a carboxylate organic solvent, wherein the carbonate organic solvent comprises one or more of methyl ethyl carbonate, diethyl carbonate, propylene carbonate, ethylene carbonate, and fluoroethylene carbonate, and the carboxylate organic solvent comprises one or more of fluoroethylene carbonate, ethyl propionate, and propyl propionate;

[0030] (4) The additive is selected from nitrile additives and ester additives, the nitrile additives include one or more of adiponitrile, glutaronitrile, succinonitrile, ethylene glycol bis (propionitrile) ether, and the ester additives include one or more of vinyl sulfate, propane sultone, citraconic anhydride, and triphenyl phosphite;

[0031] (5) In the solid electrolyte prepolymer solution, the content of the monomer is 1 to 15 wt %, and the content of the electrolyte is 85 to 99 wt %;

[0032] (6) In the electrolyte, the content of the lithium salt is 10-30wt%, the content of the additive is 1-10wt%, and the content of the organic solvent is 60-80wt%;

[0033] (7) The viscosity of the solid electrolyte prepolymer solution is in the range of 4 to 20 cP.

[0034] In a second aspect, an embodiment of the present application further provides a solid electrolyte, which is obtained by solidifying the above-mentioned solid electrolyte prepolymer solution.

[0035] Optionally, in some embodiments, the solid electrolyte satisfies the following relationship:

[0036] B×50<(T+P)×W×A <B×250;

[0037] Wherein, A is the peel strength, B is the viscosity of the solid electrolyte prepolymer solution, T is the thermal decomposition temperature of the solid electrolyte, P is the exothermic peak temperature of the solid electrolyte, and W is the mass percentage of the monomer in the solid electrolyte prepolymer solution;

[0038] Optionally, the value range of A is 20 to 200 mN / mm;

[0039] Optionally, the value range of B is 4 to 20 cP;

[0040] Optionally, the value range of T is 100 to 350°C;

[0041] Optionally, the value range of P is 100-400°C;

[0042] Optionally, the value range of W is 1-15%.

[0043] In a third aspect, an embodiment of the present application further provides a battery, comprising a positive electrode sheet, a negative electrode sheet, and the solid electrolyte.

[0044] Optionally, in some embodiments, at least one of the following features (1) to (2) is also included:

[0045] (1) A first polymer layer is bonded to the surface of the positive electrode plate, and the first polymer layer is located between the positive electrode plate and the solid electrolyte;

[0046] (2) A second polymer layer is provided on the surface of the negative electrode plate, and the second polymer layer is located between the negative electrode plate and the solid electrolyte.

[0047] Optionally, in some embodiments, at least one of the following features (1) to (3) is also included:

[0048] (1) The first polymer layer is formed by polymerizing the monomers in the solid electrolytic prepolymer solution;

[0049] (2) the second polymer layer is formed by polymerizing the monomers in the solid electrolyte prepolymer solution;

[0050] (3) The thickness of the first polymer layer and the second polymer layer are independently 5 to 200 nm

[0051] The solid electrolyte prepared from the solid electrolyte prepolymer solution described in the present application is used in batteries, which can effectively improve the heat resistance and safety performance of the batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0053] Figure 1 is a schematic diagram of the structure of a battery provided in an embodiment of the present application;

[0054] Figure 2 is a flow chart of a method for preparing a battery provided in an embodiment of the present application;

[0055] Figure 3 is a SEM image of the positive electrode sheet peeled off from the battery of Example 1 of the present application;

[0056] Figure 4 This is a SEM image of the positive electrode sheet peeled off from the battery of Comparative Example 4 of the present application;

[0057] Figure 5 is a SEM image of the negative electrode sheet peeled off from the battery of Example 1 of the present application;

[0058] Figure 6 This is a SEM image of the negative electrode sheet peeled off from the battery of Comparative Example 4 of the present application;

[0059] Figure 7 is a distance-load diagram of the peel strength of the battery of Example 1 of the present application;

[0060] Figure 8 is a differential thermal weight loss curve DTG diagram of the solid electrolyte of Example 1 of the present application;

[0061] Fig. 9 It is the differential scanning calorimetry DSC curve of the solid electrolyte of Example 1 of the present application.

[0062] Reference numerals:

[0063] Battery 100 ; positive electrode sheet 10 ; negative electrode sheet 20 ; separator 30 ; solid electrolyte 40 ; first polymer layer 50 ; second polymer layer 60 . DETAILED DESCRIPTION

[0064] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0065] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0066] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.

[0067] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0068] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or more", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0069] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0070] At present, the electrolytes used in lithium-ion batteries are mainly organic liquid electrolytes (organic electrolytes). Because they have low thermal decomposition temperature, are flammable, and easily evaporate when heated to form toxic gases, there are certain limitations in improving the safety performance and energy density of power batteries.

[0071] Liquid batteries are mainly composed of positive electrodes, negative electrodes, electrolytes, diaphragms, and external connections and packaging components. In conventional liquid batteries, the electrolyte is composed of chemical substances such as solvents, lithium salts, and additives. Due to its poor thermal stability, it is easy to decompose or even burn when heated, resulting in major safety hazards in electrochemical systems such as batteries. Internal and external factors such as battery charge and discharge overload, external short circuit, high external temperature, or internal short circuit of the battery may cause the battery to heat or generate heat and work under high temperature conditions. High temperature may cause the diaphragm to melt, the electrolyte to volatilize or even burn due to heat, and the internal structure of the battery will be damaged. A series of irreversible chemical exothermic reactions will occur between the positive and negative electrode materials, electrolytes, and foils, triggering a thermal runaway chain reaction. The heat generated in a limited space and time is high, which may cause fires and explosions, causing public safety hazards. In addition, when a liquid lithium-ion battery experiences thermal runaway at high temperatures, the solid electrolyte interface (SEI) film, lithium-embedded compounds, and electrolyte on the active material undergo irreversible thermal decomposition, a large amount of heat and combustible gases are released, and the gas pressure inside the battery rises, gradually exceeding the limit of the explosion-proof valve. When the explosion-proof valve is opened, combustible fumes and powder particles are ejected. When these combustible gases and powders come into contact with oxygen in the environment, the combustible fumes are ignited, bright sparks occur, or the battery enters a fire state.

[0072] In order to overcome these defects of liquid lithium-ion batteries, researchers began to explore the use of solid electrolytes as an alternative. Solid electrolytes are divided into two categories: inorganic solid electrolytes and polymer solid electrolytes (organic solid electrolytes). Among them, polymer solid electrolytes have attracted widespread attention due to their excellent processing performance and high adaptability to battery shape.

[0073] Compared with liquid electrolytes, the gelation of organic solid electrolytes can solve the leakage problem and has better mechanical strength and flexibility. In addition, organic solid electrolytes use intrinsically non-flammable polymer electrolytes, which are not easy to volatilize and have a higher decomposition temperature than electrolytes. Their mechanical and electrochemical properties are relatively stable, the flame retardant effect is more durable, and they can maintain good electrochemical properties at high temperatures. However, the heat resistance of existing organic solid electrolytes is not high enough and needs to be further improved.

[0074] The technical solution of this application is as follows:

[0075] In a first aspect, an embodiment of the present application provides a solid electrolyte prepolymer solution, comprising a monomer and an electrolyte.

[0076] The monomers include one or more compounds having the structural formula shown in formula (I):

[0077]

[0078] Wherein, m is any integer from 2 to 8;

[0079] L is a linking group, which can be selected from but not limited to a single bond, substituted or unsubstituted -(CH2) n1 -, substituted or unsubstituted -(CH2) n2 CH=CH(CH2) n3 -, substituted or unsubstituted -(CH2) n4 C≡C(CH2) n5 -, substituted or unsubstituted -(CH2) n6 -O-(CH2) n7 -, substituted or unsubstituted -(CH2) n8 CO(CH2) n9 -, substituted or unsubstituted amine, substituted or unsubstituted C3~C 30 Cycloalkyl, substituted or unsubstituted aryl having 6 to 60 ring atoms, and substituted or unsubstituted heteroaryl having 6 to 60 ring atoms, or a combination of two or more thereof, wherein n1 to n9 are each independently selected from an integer of 1 to 5;

[0080] R1, R2, and R3 are each independently selected from but not limited to hydrogen, substituted or unsubstituted C1-C 30 Alkyl, substituted or unsubstituted C3~C 30 The invention also comprises one or a combination of two or more of a cycloalkyl group having 6 to 60 ring atoms and a substituted or unsubstituted aryl group.

[0081] It should be noted that, in the present application, the substituents may be selected from but not limited to hydrogen, C1-C 10The invention can be selected from the group consisting of an alkyl group having 6 to 60 ring atoms and an aryl group having 6 to 60 ring atoms, or a combination of two or more thereof.

[0082] In at least one preferred embodiment, m is any integer from 2 to 4.

[0083] In some embodiments, L is selected from a single bond, a substituted or unsubstituted -(CH2) n1 -, substituted or unsubstituted -(CH2) n2 CH=CH(CH2) n3 -, substituted or unsubstituted -(CH2) n4 C≡C(CH2) n5 -, substituted or unsubstituted -(CH2) n6 -O-(CH2) n7 -, substituted or unsubstituted -(CH2) n8 CO(CH2) n9 -, substituted or unsubstituted amine, substituted or unsubstituted C3~C 20 One or a combination of two or more of a cycloalkyl group, a substituted or unsubstituted aryl group having 6 to 30 ring atoms, and a substituted or unsubstituted heteroaryl group having 6 to 30 ring atoms, wherein n1 to n9 are each independently selected from an integer of 1-5.

[0084] Further, in some embodiments, the L is selected from a single bond, a substituted or unsubstituted -(CH2) n1 -, substituted or unsubstituted -(CH2) n2 CH=CH(CH2) n3 -, substituted or unsubstituted -(CH2) n4 C≡C(CH2) n5 -, substituted or unsubstituted -(CH2) n6 -O-(CH2) n7 -, substituted or unsubstituted -(CH2) n8 CO(CH2) n9 -, substituted or unsubstituted amine, substituted or unsubstituted C3~C 10 One or a combination of two or more of a cycloalkyl group, a substituted or unsubstituted aryl group having 6 to 15 ring atoms, and a substituted or unsubstituted heteroaryl group having 6 to 15 ring atoms, wherein n1 to n9 are each independently selected from an integer of 1-5.

[0085] Further, in some embodiments, the L is selected from a single bond, a substituted or unsubstituted -(CH2) n1 -, substituted or unsubstituted -(CH2) n6 -O-(CH2) n7-, substituted or unsubstituted amino, substituted or unsubstituted cycloalkyl, substituted or unsubstituted aryl, or a combination of two or more thereof, wherein n1, n6, and n7 are each independently selected from an integer of 1 to 5.

[0086] Further, in at least some embodiments, L is selected from one or a combination of two or more of the following groups:

[0087] -(CH2) n1 -、-(CH2) n6 -O-(CH2) n7 -、

[0088] Among them, L1 to L 19 are linking groups, each independently selected from but not limited to single bonds, -(CH2) m” - any one of, wherein m' is selected from any integer of 1-5.

[0089] In some embodiments, R1, R2, and R3 are each independently selected from, but not limited to, hydrogen, substituted or unsubstituted C1-C 20 Alkyl, substituted or unsubstituted C3~C 20 The invention also comprises one or a combination of two or more of a cycloalkyl group having a ring number of 6 to 30 and a substituted or unsubstituted aryl group having a ring number of 6 to 30.

[0090] Further, in some embodiments, R1, R2, and R3 are each independently selected from but not limited to hydrogen, substituted or unsubstituted C1-C 10 Alkyl, substituted or unsubstituted C3~C 10 The invention also comprises one or a combination of two or more of a cycloalkyl group having a ring number of 6 to 20 and a substituted or unsubstituted aryl group having a ring number of 6 to 20.

[0091] Furthermore, in some embodiments, R1, R2, and R3 are each independently selected from but not limited to hydrogen, substituted or unsubstituted C1-C8 alkyl, substituted or unsubstituted C3-C8 cycloalkyl, and substituted or unsubstituted aryl having 6 to 10 ring atoms, or a combination of two or more thereof.

[0092] As an example, in some embodiments, the monomer is selected from one or more compounds represented by the following structural formulas:

[0093]

[0094] When the solid electrolyte prepolymer is heated, the monomers can be cured in situ, cross-linked with each other, and connected by chemical covalent bonds to form polymer chains. The polymer chains form a three-dimensional network structure through cross-linking points, so that the solid electrolyte prepolymer is transformed into a gel-state substance as a whole to form a solid electrolyte.

[0095] The electrolyte comprises a lithium salt, an organic solvent and an additive, and can improve the flexibility and ion conductivity of the solid electrolyte.

[0096] The lithium salt includes, but is not limited to, one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium tetrafluoroborate (LiBF4), lithium bis(oxalatoborate) (LiBOB), and lithium difluorooxalatoborate (LiDFOB). The lithium salt can act as a catalyst and an initiator, thereby in-situ curing the monomer.

[0097] The organic solvent includes, but is not limited to, one or more of a carbonate organic solvent and a carboxylate organic solvent.

[0098] In some embodiments, the carbonate organic solvent includes but is not limited to one or more of methyl ethyl carbonate (ethyl methyl carbonate, EMC), diethyl carbonate (diethyl carbonate, DEC), propylene carbonate (PC), ethylene carbonate, and fluoroethylene carbonate.

[0099] In some embodiments, the carboxylate organic solvent includes, but is not limited to, one or more of fluoroethylene carbonate (FEC), ethyl propionate (EP), and propyl propionate (PP).

[0100] The additive may be selected from but not limited to nitrile additives and ester additives. The nitrile additives include but are not limited to one or more of adiponitrile (AND), glutaronitrile, succinonitrile (SN), ethylene glycol bis (propionitrile) ether (DENE). The ester additives include but are not limited to one or more of vinyl sulfate (DTD), propane sultone (PS), citraconic anhydride, and triphenyl phosphite (TPP). The additive is a functional additive, which is used to form an electrode interface film, improve the stability of the interface, and can also reduce the impedance of the solid electrolyte prepared by the solid electrolyte prepolymer solution. Among them, triphenyl phosphite can also improve the flame retardant properties of the solid electrolyte prepared by the solid electrolyte prepolymer solution.

[0101] In some embodiments, in the solid electrolyte prepolymer, the content of the monomer is 1-15wt%, and the content of the electrolyte is 85-99wt%. Within the content range, it is beneficial to prepare a solid electrolyte with high heat resistance, thereby facilitating the preparation of a battery with good conductivity, high heat resistance, high stability and high safety.

[0102] As an example, in the solid electrolyte prepolymer, the content of the monomer can be 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, etc.

[0103] As an example, in the solid electrolyte prepolymer, the content of the electrolyte can be 85wt%, 86wt%, 87wt%, 88wt%, 89wt%, 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, 97wt%, 98wt%, 99wt%, etc.

[0104] In some embodiments, in the electrolyte, the content of the lithium salt is 10-30wt%, the content of the additive is 1-10wt%, and the content of the organic solvent is 60-80wt%. Within the above range, it is beneficial to prepare a solid electrolyte with high heat resistance, thereby preparing a battery with good conductivity, high heat resistance, high stability and high safety.

[0105] As an example, in the electrolyte, the content of the lithium salt may be 10wt%, 12wt%, 13wt%, 15wt%, 16wt%, 18wt%, 20wt%, 22wt%, 25wt%, 26wt%, 28wt%, 30wt%, etc.

[0106] As an example, in the electrolyte, the content of the additive may be 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, etc.

[0107] As an example, in the electrolyte, the content of the organic solvent can be 60wt%, 62wt%, 63wt%, 65wt%, 66wt%, 68wt%, 70wt%, 73wt%, 75wt%, 78wt%, 80wt%, etc.

[0108] In some embodiments, the viscosity of the solid electrolyte prepolymer is in the range of 4 to 20 cP, for example, 4 cP, 5 cP, 6 cP, 7 cP, 8 cP, 9 cP, 10 cP, 12 cP, 14 cP, 15 cP, 16 cP, 18 cP, 20 cP, etc. Within the viscosity range, the solid electrolyte prepolymer has good wettability to the positive and negative electrode interfaces, and can evenly cover the surface interface layer of the electrode and the electrolyte, so that the polymer layer formed by curing the solid electrolyte prepolymer evenly covers the surface interface layer of the electrode and the electrolyte.

[0109] The solid electrolyte prepolymer described in the present application has good wettability to the positive and negative electrode interfaces, and can evenly cover the surface interface layer between the electrode and the electrolyte. In addition, the solid electrolyte prepolymer forms a solid electrolyte after in-situ solidification, and compared with the lower thermal volatilization temperature of the electrolyte, the solid electrolyte has higher thermal stability.

[0110] Thermal runaway of batteries generally starts with the decomposition and heat release of the SEI film on the negative electrode side. The SEI film mainly includes an inorganic layer close to the electrode and an organic layer far away from the electrode. The properties of the inorganic layer are relatively stable, and the organic layer is relatively reactive and easy to decompose at high temperatures. When the organic components of the SEI film are exposed to air or high temperatures, they are easily decomposed and release heat. The negative electrode of the battery is generally a material coated with graphite or a carbon layer. The solvent components of the electrolyte decompose on the surface of the negative electrode to form organic components of the SEI film, generating products with high reaction activity. In the solid electrolyte prepolymer system of the present application, the monomer is in a liquid state before in-situ curing. Because it contains multiple epoxy groups, the surface tension is small, and it is more compatible with the surface of the negative electrode active material particles, which promotes the infiltration and distribution of the monomer on the surface of the negative electrode particles, and is conducive to the formation of polymer molecular chains after the monomer is heated and polymerized. A uniform interface protection layer (polymer layer) is formed in situ on the surface of the negative electrode particles. The polymer layer conducts ions but not electrons, and can conduct ions and isolate the positive and negative electrodes. When the battery is placed at high temperature, conventional polyolefin separators will shrink thermally, causing the positive and negative electrodes to contact and internally short-circuit. The highly active and high-specific-energy positive and negative electrodes will produce local short circuits, causing energy to be released locally in an instant, causing thermal runaway of the battery. The polymer layer formed by the solid electrolyte prepolymer solution of the present application can cover the surface of the negative electrode and isolate the electrons, which is beneficial to avoid thermal runaway caused by internal short circuits in the battery.

[0111] In addition, when the negative electrode of the battery is a carbon material, functional groups such as hydroxyl or carboxyl are often formed at the structural defects of the carbon layer on the surface of the negative electrode, and the epoxy groups of the monomers in the solid electrolyte prepolymer can open the ring and react with them to form chemical bonds such as ether bonds or ester bonds, thereby promoting the effective connection between the monomer molecules and the negative electrode surface, improving the adhesion of the polymer chain to the electrode interface, and making the organic solid electrolyte after in-situ curing have strong adhesion to the electrode. Further, the reaction of the epoxy groups of the monomers in the solid electrolyte prepolymer with the hydroxyl, carboxyl and other groups at the defects of the negative electrode interface can repair the surface defects of the negative electrode particles in a directional manner, so that chemical bonds with larger bond energy are formed at the defects, and the structural integrity of the defects is improved, which is beneficial to the integrity and stability of the SEI film at the negative electrode interface, and then helps to stabilize the surface structure of the negative electrode under heating.

[0112] The positive electrode of the battery is generally a metal oxide or a metal salt, and the oxidation potential is high, especially in the lithium-free state. The positive electrode active material particles themselves are unstable. When in contact with the electrolyte, redox reactions are easily generated at the interface, resulting in decomposition of the electrolyte and gas production, which aggravates the thermal runaway of the battery at high temperatures. In the solid electrolyte prepolymer system of the present application, the monomer has a large molecular dipole moment and strong polarity due to the presence of multiple epoxy groups. The organic solvent in the prepolymer is also a polar solvent, and the metal ions on the positive electrode surface have strong polarity. In this way, a good interface affinity can be generated between the solid electrolyte prepolymer and the positive electrode, promoting the infiltration of the prepolymer to the positive electrode interface and the particle gap before solidification. In addition, when the monomer is polymerized in situ to form a polymer chain, the polymer chain molecule has multiple polar groups, so that the electrolyte molecules formed by solidification can be able to produce strong interactions of complex coordination with metal ions, fixed on the surface of the positive electrode particles, and form an effective protective stabilization layer, which improves the thermal stability of the positive electrode active material at high temperatures, thereby improving the high temperature resistance of the lithium battery.

[0113] In addition, when the additive is a nitrile additive, the nitrile additive can make the electrolyte molecules and the metal center on the surface of the positive electrode produce a strong complexation, inhibit the thermal side reaction of the positive electrode material, and help to further improve the thermal stability of the battery. And the metal ion complexing the cyanide can play the role of Lewis acid, catalyzing the ring opening of the epoxy monomer, which is equivalent to the ring opening bonding of the epoxy group of the targeted catalytic monomer at the positive electrode complex to form a strong polymer coating.

[0114] The solid electrolyte prepolymer described in the present application can undergo a polymerization reaction when heated under the action of an initiator to form chemical bonds, produce a strong polymer network, and form a stable and reliable polymer gel, which absorbs the electrolyte, can effectively prevent the flow of the electrolyte and slow down its volatilization, reduce the risk of large-scale volatilization and combustion of the electrolyte when the battery is heated at high temperature, and thus improve the thermal safety of the battery.

[0115] Further, since the electrolyte is a liquid with a flowing form, it is impossible to form an effective bond on the active electrode surface, and the material composition and concentration at the interface will often change, which will affect the stable operation of the electrode interface. The epoxy groups of the monomers in the solid electrolyte prepolymer of the present application are ring-opened to generate ether oxygen bonds, so that the main chain of the cured molecular chain contains ether oxygen bonds, thereby giving the polymer molecular chain flexibility, presenting a flexible and disordered molecular conformation, allowing the molecular groups to stretch freely, and easily interacting with the lithium salt and solvent in the electrolyte, improving the dissolution and absorption capacity of the main chain of the molecule for lithium salt and electrolyte, further improving the flexibility of the chain segment, making the polymer chain more mobile, and having a smaller diffusion resistance at the electrode surface interface, and improving the wetting and bonding effect of the polymer chain at the electrode surface interface, which is conducive to improving the bonding ability of the polymer chain, so that the polymer is firmly fixed on the electrode surface, forming a stable electrode and electrolyte interface, thereby improving the interface stability and battery thermal safety.

[0116] Furthermore, after in-situ thermal curing, the monomers containing multiple epoxy groups in the solid electrolyte prepolymer form polymer molecular chains with a cross-linked network structure, constructing a gel system with excellent strength and easy absorption of electrolyte, which can effectively solve the leakage caused by the flow of electrolyte and slow down the volatilization of electrolyte. At the same time, the thermal decomposition temperature of the polymer cross-linked network is relatively high, it is difficult to thermally decompose itself, and has strong high-temperature stability, which can reduce the risk of large-scale volatilization and combustion of electrolyte under high-temperature heating, thereby improving the thermal safety of the battery.

[0117] In some embodiments, the method for preparing the solid electrolyte prepolymer solution includes: mixing a monomer and an electrolyte in proportion to obtain the solid electrolyte prepolymer solution.

[0118] In a second aspect, an embodiment of the present application further provides a solid electrolyte, which is obtained by solidifying the solid electrolyte prepolymer liquid described above.

[0119] The solid electrolyte satisfies the following relationship:

[0120] B×50<(T+P)×W×A <B×250;

[0121] Wherein, A is the peel strength, B is the viscosity of the solid electrolyte prepolymer solution, T is the thermal decomposition temperature of the solid electrolyte, P is the exothermic peak temperature of the solid electrolyte, and W is the mass percentage of the monomer in the solid electrolyte prepolymer solution.

[0122] The value range of A is 20 to 200 mN / mm, for example, 20 mN / mm, 30 mN / mm, 50 mN / mm, 60 mN / mm, 80 mN / mm, 100 mN / mm, 120 mN / mm, 130 mN / mm, 150 mN / mm, 160 mN / mm, 180 mN / mm, 200 mN / mm, etc.

[0123] The value range of B is 4 to 20 cP, for example, 4 cP, 5 cP, 6 cP, 7 cP, 8 cP, 9 cP, 10 cP, 12 cP, 14 cP, 15 cP, 16 cP, 18 cP, 20 cP, etc.

[0124] The value range of T is 100-350°C, for example, 100°C, 120°C, 150°C, 160°C, 180°C, 200°C, 220°C, 230°C, 250°C, 260°C, 280°C, 300°C, 320°C, 330°C, 350°C, etc.

[0125] The value range of P is 100-400°C, for example, 100°C, 120°C, 150°C, 160°C, 180°C, 200°C, 220°C, 250°C, 260°C, 280°C, 300°C, 320°C, 330°C, 350°C, 360°C, 380°C, 400°C, etc.

[0126] The value range of W is 1-15%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, etc.

[0127] Solid electrolytes that meet the requirements of the above numerical relationship can, on the one hand, form good infiltration and coverage on the surfaces of the positive and negative electrodes, effectively protect the active interface, and inhibit the side reactions of the positive and negative electrodes at high temperatures; on the other hand, they have good heat resistance and can withstand higher temperatures; on the other hand, they have good adhesion to the surfaces of the positive and negative electrodes, can firmly adhere to the active surface, and well isolate the positive and negative electrodes to prevent internal short circuits in the battery.

[0128] Third, see Figure 1 The embodiment of the present application further provides a battery 100, comprising a positive electrode sheet 10, a negative electrode sheet 20, a separator 30 and the solid electrolyte 40 described above.

[0129] The surface of the positive electrode plate 10 is combined with a first polymer layer 50, and the first polymer layer 50 is located between the positive electrode plate 10 and the solid electrolyte 40. The first polymer layer 50 is formed by solidifying the monomer in the solid electrolyte prepolymer solution. The first polymer layer 50 has a strong bonding force with the positive electrode plate 10, which can effectively protect the battery 100, isolate the positive electrode and the negative electrode of the battery, avoid conduction between the positive electrode and the negative electrode, and effectively improve the thermal stability and safety performance of the battery 100.

[0130] It can be understood that the first polymer layer 50 is formed by polymerizing the monomers in the solid electrolyte prepolymer solution.

[0131] The surface of the negative electrode plate 20 has a second polymer layer 60, and the second polymer layer 60 is located between the negative electrode plate 20 and the solid electrolyte 40. The second polymer layer 60 is formed by solidifying the monomer in the solid electrolyte prepolymer solution. The second polymer layer 60 has a strong bonding force with the negative electrode plate 20, which can effectively protect the battery 100, isolate the positive electrode and the negative electrode of the battery, avoid conduction between the positive electrode and the negative electrode, and effectively improve the thermal stability and safety performance of the battery.

[0132] It can be understood that the second polymer layer 60 is formed by polymerizing the monomers in the solid electrolyte prepolymer solution.

[0133] The thickness of the first polymer layer 50 and the second polymer layer 60 are independently 5 to 200 nm, for example, 5 nm, 10 nm, 30 nm, 50 nm, 60 nm, 80 nm, 1000 nm, 120 nm, 130 nm, 150 nm, 160 nm, 180 nm, 200 nm, etc. Within the thickness range, the positive electrode and the negative electrode of the battery can be effectively isolated, and the thermal stability and safety performance of the battery can be effectively improved.

[0134] It is understandable that the battery described in the present application is a solid-state battery. In some embodiments, the solid-state battery is a lithium-ion solid-state battery.

[0135] Fourth, please refer to Figure 2 The present application also provides a method for preparing a battery, comprising the following steps:

[0136] Step S11, mixing the monomer and the electrolyte in proportion to obtain a solid electrolyte prepolymer solution;

[0137] Step S12, injecting the solid electrolyte prepolymer into a dry battery cell consisting of a positive electrode plate, a negative electrode plate and a separator, and heat treating the solid electrolyte prepolymer to solidify the monomers in the solid electrolyte prepolymer to form a solid electrolyte, thereby obtaining a battery.

[0138] In the step S11:

[0139] The types and proportions of the monomers and the electrolyte are as described above and will not be repeated here.

[0140] In step S12:

[0141] After the solid electrolyte prepolymer is injected into the dry battery cell consisting of a positive electrode sheet, a negative electrode sheet and a separator, the method further includes: pre-packaging and standing at room temperature for 24 to 72 hours.

[0142] In some embodiments, the pre-packaging is performed using a heat-sealing machine.

[0143] In some embodiments, the heat treatment temperature is 40 to 80°C, for example, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc., and the time is 6 to 48 hours, for example, 6 hours, 10 hours, 15 hours, 20 hours, 25 hours, 30 hours, 35 hours, 40 hours, 45 hours, 48 ​​hours, etc. Within the temperature and time range, the solid electrolyte prepolymer solution can be effectively solidified, and a stable polymer coating can be formed on the surface of the positive electrode sheet and the negative electrode sheet, which is conducive to preparing a battery with high thermal stability and safety.

[0144] The present application is described in detail below by means of specific examples, which are only partial examples of the present application and are not intended to limit the present application. The raw materials used in the following examples are all commercially available products unless otherwise specified.

[0145] Example 1

[0146] Preparation of solid electrolyte prepolymer solution:

[0147] Providing an electrolyte, the electrolyte comprising an organic solvent, an additive and a lithium salt, wherein the organic solvent comprises 30 g of ethyl methyl carbonate, 20 g of diethyl carbonate, 16 g of propylene carbonate, 7 g of ethylene carbonate, and 6 g of fluoroethylene carbonate, the additive comprises 3.8 g of adiponitrile and 0.2 g of citraconic anhydride, and the lithium salt comprises 10 g of lithium hexafluorophosphate and 5 g of lithium bis(fluorosulfonyl)imide;

[0148] 2 g of monomer 1 was mixed with 98 g of electrolyte, and mixed evenly at room temperature in a drying room (relative humidity below 2%, dew point below -40°C) to obtain a solid electrolyte prepolymer solution.

[0149] Solid-state battery preparation:

[0150] The positive electrode active material lithium nickel cobalt manganese oxide NCM811 accounting for 97% by mass and the conductive agent acetylene black accounting for 1% by mass are ground and mixed, polyvinylidene fluoride PVDF accounting for 2% by mass are added, and then added into a solvent 1-methyl-2-pyrrolidone NMP for grinding and mixing to obtain a positive electrode material, wherein NMP is used for mixing, dispersing and adjusting the viscosity of the slurry, and volatilizes during drying, so it is not included in the mass percentage of the positive electrode material, and the positive electrode material is coated on the surface of aluminum foil, and dried to obtain a positive electrode;

[0151] 96% by weight of silicon-oxygen-carbon composite negative electrode material is added to 1% by weight of conductive carbon black SP, and ground and mixed, 1% by weight of sodium carboxymethyl cellulose CMC and 2% by weight of polystyrene butadiene copolymer SBR are added, and then put into water for mixing, ground and dispersed, and coated on the surface of copper foil, and dried to obtain a negative electrode sheet;

[0152] Assembling the positive electrode sheet, the negative electrode sheet and the separator to obtain a dry battery cell, wherein the separator is a three-layer separator of polypropylene / polyethylene / polypropylene, i.e., PP / PE / PP separator, and the total thickness of the separator is 12 microns;

[0153] The solid electrolyte prepolymer is injected into the dry battery cell, where it is pre-sealed with a heat plastic sealing machine, left to stand at room temperature for 24 hours, and then placed in a hot oven, slowly heated to 60°C, and reacted for 24 hours. During the standing and heating, the electrolyte prepolymer reacts inside the dry battery cell, and a solid electrolyte is obtained by in-situ thermal curing to prepare a solid-state battery.

[0154] Example 2

[0155] This embodiment is basically the same as Embodiment 1, except that:

[0156] In this embodiment, the preparation method of the solid electrolyte prepolymer solution includes:

[0157] Providing an electrolyte, the electrolyte comprising an organic solvent, an additive and a lithium salt, wherein the organic solvent comprises 30 g of ethyl methyl carbonate, 20 g of diethyl carbonate, 16 g of propylene carbonate, 6 g of ethylene carbonate, and 6 g of fluoroethylene carbonate, the additive comprises 3.8 g of adiponitrile and 0.2 g of citraconic anhydride, and the lithium salt comprises 10 g of lithium hexafluorophosphate and 5 g of lithium bis(fluorosulfonyl)imide;

[0158] 3 g of monomer 2 was mixed with 97 g of electrolyte, and mixed evenly at room temperature in a drying room (relative humidity below 2%, dew point below -40°C) to obtain a solid electrolyte prepolymer solution.

[0159] The solid-state battery of this embodiment is slowly heated to 50° C. during preparation.

[0160] Example 3

[0161] This embodiment is basically the same as Embodiment 1, except that, in this embodiment, the monomer 3 described above is used to replace the monomer 1 in Embodiment 1, the organic solvent of this embodiment includes 25 g of diethyl carbonate, 25 g of dimethyl carbonate, 13 g of ethylene carbonate, 7 g of ethyl propionate, and 6 g of fluoroethylene carbonate, the additives of this embodiment include 5.2 g of succinonitrile, 1.0 g of propane sultone, and 0.8 g of triphenyl phosphate, and the lithium salt of this embodiment includes 10 g of lithium bis(fluorosulfonyl)imide and 5 g of lithium bis(trifluoromethylsulfonyl)imide.

[0162] Example 4

[0163] This embodiment is basically the same as Embodiment 1, except that this embodiment uses monomer 4 to replace monomer 1 in Embodiment 1.

[0164] Example 5

[0165] This embodiment is basically the same as Embodiment 1, except that this embodiment uses monomer 5 to replace monomer 1 in Embodiment 1.

[0166] Example 6

[0167] This embodiment is basically the same as Embodiment 1, except that this embodiment uses monomer 6 to replace monomer 1 in Embodiment 1.

[0168] Example 7

[0169] This embodiment is basically the same as Embodiment 1, except that this embodiment uses monomer 7 to replace monomer 1 in Embodiment 1.

[0170] Example 8

[0171] This embodiment is basically the same as Embodiment 1, except that this embodiment uses monomer 8 to replace monomer 1 in Embodiment 1.

[0172] Example 9

[0173] This embodiment is basically the same as Embodiment 1, except that this embodiment uses monomer 9 to replace monomer 1 in Embodiment 1.

[0174] Example 10

[0175] This embodiment is substantially the same as the embodiment 1, except that the monomer 10 is used to replace the monomer 1 in the embodiment 1.

[0176] Embodiment 11

[0177] This embodiment is basically the same as Embodiment 1, except that this embodiment uses monomer 11 to replace monomer 1 in Embodiment 1.

[0178] Example 12

[0179] This embodiment is basically the same as Embodiment 1, except that this embodiment uses monomer 12 to replace monomer 1 in Embodiment 1.

[0180] Embodiment 13

[0181] This embodiment is basically the same as Embodiment 1, except that this embodiment uses monomer 13 to replace monomer 1 in Embodiment 1.

[0182] Embodiment 14

[0183] This embodiment is substantially the same as Embodiment 1, except that, in the lithium electrolyte of this embodiment, the organic solvent is 79 g of ethyl methyl carbonate, the additive is 4 g of adiponitrile, and the lithium salt is 15 g of lithium hexafluorophosphate.

[0184] Embodiment 15

[0185] This embodiment is basically the same as Embodiment 1, except that, in this embodiment, 5 g of monomer 1 is mixed with 95 g of electrolyte, and the organic solvent of this embodiment includes 28 g of ethyl methyl carbonate, 20 g of diethyl carbonate, 15 g of propylene carbonate, 7 g of ethylene carbonate, and 6 g of fluoroethylene carbonate.

[0186] Example 16

[0187] This embodiment is basically the same as Embodiment 1, except that, in this embodiment, 15 g of monomer 1 is mixed with 85 g of electrolyte, and the organic solvent of this embodiment includes 20 g of ethyl methyl carbonate, 18 g of diethyl carbonate, 15 g of propylene carbonate, 7 g of ethylene carbonate, and 6 g of fluoroethylene carbonate.

[0188] Embodiment 17

[0189] This embodiment is basically the same as Embodiment 14, except that, in the lithium electrolyte of this embodiment, the organic solvent is 84 g of ethyl methyl carbonate, the additive is 4 g of adiponitrile, and the lithium salt is 10 g of lithium hexafluorophosphate.

[0190] Embodiment 18

[0191] This embodiment is basically the same as Embodiment 14, except that, in the lithium electrolyte of this embodiment, the organic solvent is 64 g of ethyl methyl carbonate, the additive is 4 g of adiponitrile, and the lithium salt is 30 g of lithium hexafluorophosphate.

[0192] Embodiment 19

[0193] This embodiment is basically the same as Embodiment 14, except that, in the lithium electrolyte of this embodiment, the organic solvent is 82 g of ethyl methyl carbonate, the additive is 1 g of adiponitrile, and the lithium salt is 15 g of lithium hexafluorophosphate.

[0194] Embodiment 20

[0195] This embodiment is basically the same as Embodiment 14, except that, in the lithium electrolyte of this embodiment, the organic solvent is 73 g of ethyl methyl carbonate, the additive is 10 g of adiponitrile, and the lithium salt is 15 g of lithium hexafluorophosphate.

[0196] Embodiment 21

[0197] This embodiment is substantially the same as embodiment 1, except that in this embodiment, the temperature is slowly heated to 40°C.

[0198] Embodiment 22

[0199] This embodiment is substantially the same as embodiment 1, except that in this embodiment, the temperature is slowly heated to 80°C.

[0200] Comparative Example 1

[0201] This comparative example is substantially the same as Example 1, except that the monomer 1 in Example 1 is replaced by the comparative monomer 1 in this comparative example.

[0202] The chemical structure of the comparative monomer 1 is:

[0203]

[0204] Comparative Example 2

[0205] This comparative example is basically the same as Example 1, except that the comparative example uses comparative monomer 2 to replace monomer 1 in Example 1.

[0206] The chemical structure of the comparative monomer 2 is:

[0207]

[0208] Comparative Example 3

[0209] This comparative example is basically the same as Example 1, except that the electrolyte in this comparative example includes an organic solvent and a lithium salt (excluding additives), the organic solvent includes 30 g of ethyl methyl carbonate and 20 g of diethyl carbonate, and the lithium salt includes 10 g of lithium hexafluorophosphate; and in this comparative example, 40 g of comparison monomer 3 is mixed with 60 g of the electrolyte.

[0210] The chemical structure of the comparative monomer 3 is:

[0211]

[0212] Comparative Example 4

[0213] This comparative example is substantially the same as Example 1, except that the solid electrolyte prepolymer solution of this example does not contain monomers.

[0214] The solid-state batteries of Example 1 and Comparative Example 4 were formed: charged with 0.02C constant current for 60 min, 0.05C constant current for 60 min, 0.1C constant current for 120 min, 0.2C constant current for 180 min, with an upper limit voltage of 3.9 V, and then charged and discharged with a current of 1C first at constant current and then at constant voltage, i.e., CC-CV mode, with a cut-off voltage of 2.75-4.2 V. The positive and negative pole pieces of the formed batteries were peeled off from the solid electrolyte to obtain the positive and negative pole pieces of the solid-state battery of Example 1 and the positive and negative pole pieces of the solid-state battery of Comparative Example 4, respectively. Then, the surfaces of the positive and negative pole pieces that were originally in contact with the solid electrolyte were subjected to SEM tests, respectively, to obtain Figure 3 The SEM image of the positive electrode sheet peeled off from the battery of Example 1 is shown. Figure 4 The SEM image of the positive electrode sheet of Comparative Example 4 peeled off from the battery shown, Figure 5 The SEM image of the negative electrode sheet peeled off from the battery of Example 1 is shown. Figure 6 The SEM image of the negative electrode sheet peeled off from the battery of Comparative Example 4 is shown.

[0215] Depend on Figure 3 and Figure 4 It can be seen that the surface morphology of the positive electrode sheet peeled from the solid-state battery of Example 1 is significantly different from the surface morphology of the positive electrode sheet peeled from the solid-state battery of Comparative Example 4, and there is obvious material attached to the surface of the positive electrode sheet peeled from the solid-state battery of Example 1. It can be seen that the monomer in Example 1 forms a relatively uniform polymer layer in situ on the surface of the positive electrode sheet.

[0216] Depend on Figure 5 and Figure 6 It can be seen that the surface morphology of the negative electrode sheet peeled off from the solid-state battery of Example 1 is significantly different from the surface morphology of the negative electrode sheet peeled off from the solid-state battery of Comparative Example 4. There is obvious material attached to the surface of the negative electrode sheet peeled off from the solid-state battery of Example 1, forming a first polymer layer. It can be seen that the monomer in Example 1 forms a relatively uniform polymer layer in situ on the surface of the negative electrode sheet.

[0217] The viscosity of the solid electrolyte prepolymer solutions of Examples 1 to 22 and Comparative Examples 1 to 3 was tested. The test results are shown in Table 1.

[0218] The batteries of Examples 1 to 22 and Comparative Examples 1 to 3 were formed: charged with 0.02C constant current for 60 min, 0.05C constant current for 60 min, 0.1C constant current for 120 min, 0.2C constant current for 180 min, with an upper limit voltage of 3.9 V, and then charged and discharged with a current of 1C first at a constant current and then at a constant voltage, i.e., CC-CV mode, with a cut-off voltage of 2.75 to 4.2 V.

[0219] The formed battery was tested for the peel strength between the electrode and the solid electrolyte, the thermal decomposition temperature of the solid electrolyte, and the peak temperature of the thermal enthalpy of the solid electrolyte. The test results are shown in Table 1 and Figures 7 to 9 ,in, Figure 7 This is the distance-load diagram of the peel strength of the battery of Example 1, Figure 8 The differential thermal weight loss curve DTG diagram of the solid electrolyte of Example 1 is shown in FIG. Fig. 9 The differential scanning calorimetry (DSC) curve of the solid electrolyte of Example 1 is shown in FIG.

[0220] The viscosity test method is as follows: Use NDJ-5S digital display rotary viscometer to test the viscosity of solid electrolyte prepolymer liquid, pour the solid electrolyte prepolymer liquid into a flat-bottom container with a diameter greater than 60mm, maintain the temperature of the solid electrolyte prepolymer liquid at 25°C, and the operating table is stable and vibration-free. Screw the instrument protection frame into the lower end of the instrument in reverse, use the L0 rotor to screw it counterclockwise into the instrument universal joint, rotate the lifting knob, and slowly immerse the rotor in the solid electrolyte prepolymer liquid until the rotor liquid level mark, that is, the groove scale, is in the same plane as the liquid surface, and adjust the instrument level again. Press the rotor selection key, select the speed and then press the confirmation key. The rotor starts to rotate, and after the displayed value stabilizes, press the stop key to read the viscosity value.

[0221] The peel strength was tested according to the IPC-TM-6502.8 method: using the Shimadzu AG-X 50N stripper. Wipe the mirror steel plate with alcohol, and stick the double-sided tape on the mirror copper plate. During the gluing process, it is necessary to ensure that the tape and the steel plate are firmly bonded without bubbles. The discharged battery was disassembled to obtain a single battery chip material with positive electrode, diaphragm and negative electrode. The three were covered with an organic solid electrolyte electrode sheet. The two sides of the battery chip material were metal foil materials, the positive electrode surface was aluminum foil, and the negative electrode surface was copper foil. The electrode sheet was cut into small strips of 25mm*220mm. One side of the positive aluminum foil was bonded to the steel plate with double-sided tape. The electrode sheet was parallel to the steel plate and rolled back and forth 3 times with an automatic roller. The stripper was turned on, the stripping speed was set to 50mm / min, the lower clamp clamped the steel plate, and the upper clamp clamped the smooth copper foil of the negative electrode sheet. Zeroing and starting the test, each material was tested 5 times, and the average value was taken. According to the formula: A = F / L, where A is the peel strength in mN / mm, F is the average peel force in mN, and L is the sample test width in mm;

[0222] Thermal decomposition temperature test: The solid electrolyte prepolymer solution was prepared by the method of Examples 1 to 22 and Comparative Examples 1 to 3, and then the solid electrolyte was cured by the curing method of the solid electrolyte prepolymer solution of Examples 1 to 22 and Comparative Examples 1 to 3, respectively. 10 mg of each solid electrolyte was weighed with a microbalance, and the thermogravimetric analyzer TGA5500 was preheated for 3 hours. The weighed solid electrolyte was then placed in a small ceramic crucible, and the instrument parameters of the thermogravimetric analyzer TGA5500 were set, and the temperature was heated from 35°C to 850°C at a heating rate of 10°C / min. Nitrogen was passed during the test, and the ventilation rate was 40 mL / min. The relationship between the mass loss ratio and the temperature was obtained, and the TG was derived and differentiated to obtain the differential thermogravimetric curve DTG. The temperature corresponding to the DTG peak was read, which was defined as the thermal decomposition temperature T (°C);

[0223] Exothermic peak temperature test: The solid electrolyte prepolymer was prepared by the method of Examples 1 to 22 and Comparative Examples 1 to 3, and then the solid electrolyte was solidified by the solidification method of the solid electrolyte prepolymer of Examples 1 to 22 and Comparative Examples 1 to 3, respectively. 10 mg of each solid electrolyte was weighed with a microbalance, and the DSC instrument was preheated for 3 hours. Then the weighed solid electrolyte was placed in a high-pressure crucible, and pressed and sealed with a press. The DSC instrument parameters were set, and the temperature was heated from 35°C to 600°C at a heating rate of 5°C / min. Nitrogen was passed through the test, and the ventilation rate was 40 mL / min. The relationship curve between heat flow rate and temperature DSC was obtained, and the temperature corresponding to the highest exothermic peak was read, which was the exothermic peak temperature P (°C).

[0224] Table 1:

[0225]

[0226]

[0227]

[0228] Depend on Figure 7 It can be seen that the solid electrolyte film has excellent adhesion to the surface of the positive and negative electrodes, and exhibits high peel strength, which can ensure efficient bonding between the polymer electrolyte and the positive and negative electrode active materials. During the battery charging and discharging process, the positive and negative electrode active materials undergo phase changes, resulting in volume shrinkage and expansion. The high bonding peel strength can ensure effective contact between the positive and negative electrodes and the electrolyte, and improve the interfacial stability of the battery. At the same time, under high external temperature, the diaphragm of the battery in the conventional system shrinks at high temperatures such as over 150°C, resulting in a short circuit between the positive and negative electrodes, and then violent heat release. In the organic solid electrolyte protected by this patent, it can form a bond with the positive and negative electrodes, effectively adsorb the diaphragm, and firmly bond to the surface of the electrode piece, avoiding short circuits and violent heat release caused by large-area contact between the positive and negative electrodes due to heat, thereby improving the high temperature resistance of the battery.

[0229] It can be seen from Figure 8 that: The DTG curve of the solid electrolyte in Example 1 shows the temperature corresponding to the fastest thermal weight loss rate, that is, the defined thermal decomposition temperature T is 201 °C, which is much higher than the operating temperature of conventional batteries, indicating that the application of the organic solid electrolyte can improve the thermal safety performance of the battery. Before the thermal decomposition temperature T, some solvents volatilize due to heat at high temperature, resulting in weight loss. As the temperature increases, the weight loss caused by solvent volatilization becomes more obvious. This part of solvent volatilization absorbs heat due to its own thermal evaporation, slowing down the rate of temperature rise.

[0230] It can be seen from Fig. 9 that: The DSC curve of the organic solid electrolyte in Example 1 shows the relationship between the energy difference transmitted to the sample and the reference blank sample and temperature. The maximum enthalpy change appears at 210 °C, corresponding to exothermic reactions such as partial destruction and decomposition of the cross-linked structure of the organic solid electrolyte in the high-pressure crucible. There is an endothermic hump in the temperature range before this, corresponding to the slow volatilization and endothermic effect of the solvent in the electrolyte. This DSC curve shows that the peak enthalpy temperature of the organic solid electrolyte is much higher than the conventional heat resistance temperature of the battery, and its application can improve the thermal safety performance of the battery.

[0231] It can be seen from Table 1 that: The solid electrolytes of Examples 1 to 22 satisfy the relational expression B×50 < (T + P)×W×A < B×250 described above; compared with the batteries of Comparative Examples 1 to 4, the battery of Example 22 has a higher thermal decomposition temperature and a higher peak enthalpy temperature; it can be seen that the solid-state battery prepared by using the solid electrolyte prepolymer solution described in this application has high thermal stability and thus can have high safety.

[0232] The technical solutions provided in the embodiments of the present application have been introduced in detail above. Specific examples are used in this article to elaborate on the principles and implementation manners of the present application. The description of the above embodiments is only used to help understand the method and its core idea of the present application; at the same time, for those skilled in the art, according to the idea of the present application, there will be changes in the specific implementation manners and application scopes. In summary, the content of this specification should not be construed as a limitation to the present application.

Claims

1. A solid electrolyte prepolymer solution, characterized in that: The invention comprises a monomer and an electrolyte, wherein the electrolyte comprises a lithium salt, an organic solvent and an additive, and the monomer comprises one or more compounds having a structural formula shown in formula (I): Wherein, m is any integer from 2 to 8; L is a linking group selected from a single bond, substituted or unsubstituted -(CH2) n1 -, substituted or unsubstituted -(CH2) n2 CH=CH(CH2) n3 -, substituted or unsubstituted -(CH2) n4 C≡C(CH2) n5 -, substituted or unsubstituted -(CH2) n6 -O-(CH2) n7 -, substituted or unsubstituted -(CH2) n8 CO(CH2) n9 -, substituted or unsubstituted amine, substituted or unsubstituted C3~C 30 Cycloalkyl, substituted or unsubstituted aryl having 6 to 60 ring atoms, and substituted or unsubstituted heteroaryl having 6 to 60 ring atoms, or a combination of two or more thereof, wherein n1 to n9 are each independently selected from an integer of 1 to 5; R1, R2, and R3 are each independently selected from hydrogen, substituted or unsubstituted C1-C 30 Alkyl, substituted or unsubstituted C3~C 30 The invention also comprises one or a combination of two or more of a cycloalkyl group having 6 to 60 ring atoms and a substituted or unsubstituted aryl group.

2. The solid electrolyte prepolymer solution according to claim 1, characterized in that The invention comprises at least one of the following features (1) to (2): (1) L is selected from a single bond, a substituted or unsubstituted -(CH2) n1 -, substituted or unsubstituted -(CH2) n2 CH=CH(CH2) n3 -, substituted or unsubstituted -(CH2) n4 C≡C(CH2) n5 -, substituted or unsubstituted -(CH2) n6 -O-(CH2) n7 -, substituted or unsubstituted -(CH2) n8 CO(CH2) n9 -, substituted or unsubstituted amine, substituted or unsubstituted C3~C 20 Cycloalkyl, substituted or unsubstituted aryl having 6 to 30 ring atoms, and substituted or unsubstituted heteroaryl having 6 to 30 ring atoms, or a combination of two or more thereof, wherein n1 to n9 are each independently selected from an integer of 1 to 5; (2) R1, R2, and R3 are each independently selected from hydrogen, substituted or unsubstituted C1-C 20 Alkyl, substituted or unsubstituted C3~C 20 The invention also comprises one or a combination of two or more of a cycloalkyl group having a ring number of 6 to 30 and a substituted or unsubstituted aryl group having a ring number of 6 to 30.

3. The solid electrolyte prepolymer solution according to claim 1, characterized in that The invention comprises at least one of the following features (1) to (2): (1) L is selected from a single bond, a substituted or unsubstituted -(CH2) n1 -, substituted or unsubstituted -(CH2) n2 CH=CH(CH2) n3 -, substituted or unsubstituted -(CH2) n4 C≡C(CH2) n5 -, substituted or unsubstituted -(CH2) n6 -O-(CH2) n7 -, substituted or unsubstituted -(CH2) n8 CO(CH2) n9 -, substituted or unsubstituted amine, substituted or unsubstituted C3~C 10 Cycloalkyl, substituted or unsubstituted aryl having 6 to 15 ring atoms, and substituted or unsubstituted heteroaryl having 6 to 15 ring atoms, or a combination of two or more thereof, wherein n1 to n9 are each independently selected from an integer of 1 to 5; (2) R1, R2, and R3 are each independently selected from hydrogen, substituted or unsubstituted C1-C 10 Alkyl, substituted or unsubstituted C3~C 10 The invention also comprises one or a combination of two or more of a cycloalkyl group having a ring number of 6 to 20 and a substituted or unsubstituted aryl group having a ring number of 6 to 20.

4. The solid electrolyte prepolymer solution according to claim 1, characterized in that The invention comprises at least one of the following features (1) to (2): (1) L is selected from a single bond, a substituted or unsubstituted -(CH2) n1 -, substituted or unsubstituted -(CH2) n6 -O-(CH2) n7 -, a substituted or unsubstituted amino group, a substituted or unsubstituted cycloalkyl group, a substituted or unsubstituted aryl group, or a combination of two or more thereof, wherein n1, n6, and n7 are each independently selected from an integer of 1 to 5; (2) R1, R2, and R3 are each independently selected from one or a combination of two or more of hydrogen, substituted or unsubstituted C1-C8 alkyl, substituted or unsubstituted C3-C8 cycloalkyl, and substituted or unsubstituted aryl having 6 to 10 ring atoms.

5. The solid electrolyte prepolymer solution according to claim 1, characterized in that The L is selected from one or a combination of two or more of the following groups: -(CH2) n1 -、-(CH2) n6 -O-(CH2) n7 -、 Among them, L1 to L 19 is a linking group, each independently selected from a single bond, -(CH2) m’ - any one of, wherein m' is selected from any integer of 1-5.

6. The solid electrolyte prepolymer solution according to claim 1, characterized in that: The monomer is selected from one or more compounds represented by the following structural formula:

7. The solid electrolyte prepolymer solution according to claim 1, characterized in that: The method comprises at least one of the following features (1) to (7): (1) m is any integer from 2 to 4; (2) The lithium salt includes one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluoroborate, lithium bis(oxalatoborate), and lithium difluorooxalatoborate; (3) the organic solvent comprises one or more of a carbonate organic solvent and a carboxylate organic solvent, wherein the carbonate organic solvent comprises one or more of methyl ethyl carbonate, diethyl carbonate, propylene carbonate, ethylene carbonate, and fluoroethylene carbonate, and the carboxylate organic solvent comprises one or more of fluoroethylene carbonate, ethyl propionate, and propyl propionate; (4) The additive is selected from nitrile additives and ester additives, the nitrile additives include one or more of adiponitrile, glutaronitrile, succinonitrile, ethylene glycol bis (propionitrile) ether, and the ester additives include one or more of vinyl sulfate, propane sultone, citraconic anhydride, and triphenyl phosphite; (5) In the solid electrolyte prepolymer solution, the content of the monomer is 1 to 15 wt %, and the content of the electrolyte is 85 to 99 wt %; (6) In the electrolyte, the content of the lithium salt is 10-30wt%, the content of the additive is 1-10wt%, and the content of the organic solvent is 60-80wt%; (7) The viscosity of the solid electrolyte prepolymer solution is in the range of 4 to 20 cP.

8. A solid electrolyte, characterized in that The solid electrolyte is obtained by solidifying the solid electrolyte prepolymer solution according to any one of claims 1 to 7.

9. The solid electrolyte according to claim 8, characterized in that The solid electrolyte satisfies the following relationship: B×50<(T+P)×W×A <B×250; Wherein, A is the peel strength, B is the viscosity of the solid electrolyte prepolymer solution, T is the thermal decomposition temperature of the solid electrolyte, P is the exothermic peak temperature of the solid electrolyte, and W is the mass percentage of the monomer in the solid electrolyte prepolymer solution; Optionally, the value range of A is 20 to 200 mN / mm; Optionally, the value range of B is 4 to 20 cP; Optionally, the value range of T is 100 to 350°C; Optionally, the value range of P is 100-400°C; Optionally, the value range of W is 1-15%.

10. A battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, and the solid electrolyte according to any one of claims 8 to 9.

11. The battery according to claim 10, characterized in that The invention comprises at least one of the following features (1) to (2): (1) A first polymer layer is bonded to the surface of the positive electrode plate, and the first polymer layer is located between the positive electrode plate and the solid electrolyte; (2) A second polymer layer is provided on the surface of the negative electrode plate, and the second polymer layer is located between the negative electrode plate and the solid electrolyte.

12. The battery according to claim 11, characterized in that The invention comprises at least one of the following features (1) to (3): (1) The first polymer layer is formed by polymerizing the monomers in the solid electrolytic prepolymer solution; (2) the second polymer layer is formed by polymerizing the monomers in the solid electrolyte prepolymer solution; (3) The thickness of the first polymer layer and the second polymer layer are each independently 5 to 200 nm.

Citation Information

Patent Citations

  • Method of preparing gel polymer electrolyte secondary battery and gel polymer electrolyte secondary battery

    CN102119462A

  • Gel electrolyte and preparation method thereof, negative electrode, lithium battery and vehicle

    CN115528299A

  • Solid electrolyte and polymer solid electrolyte battery

    JP2002343431A

  • Modified sulfide solid electrolyte and production method for same, and electrode combined material and lithium-ion battery

    WO2023190625A1

  • KR20210045136A

Cited By

  • Lithium metal battery low-enthalpy-change high-safety semi-solid electrolyte and preparation method and application thereof

    CN120767402A